Pembuatan Websiteonline Penjualan Jam Tangan Menggunakan Framework PHP Codeigniter dan MySQL - Ravi Abdallah; Adam Huda Nugraha (Lembaga Pengembangan Kinerja Dosen, 2023)
This online shop is a business that sells watches. This online shop previously implemented a transaction system, namely that buyers came directly to the location and paid for the products they purchased and could not make transactions outside of the shop. In promotions, the shop only offers new goods to buyers who come to the shop. This means that product promotion and marketing is not optimal. Other obstacles often faced by watch sellers include inaccurate recording of incoming turnover, as well as the number of watches in stock in the shop not being properly recorded. Seeing the condition of the problem, creating a website http://jamtanganonline.my.id/ was deemed appropriate as a solution. The aim of creating this Online Watch website is to make it easier for buyers to shop online and make it easier for sellers to promote and manage the number of watches in stock. Application creation is carried out using the Waterfall method. In the design stage, the author designed the Navigation Structure, UML Design and Database Structure Design. At the program creation stage, use the Sublime Text text editor using the CodeIgniter Framework, the PHP programming language and the use of MySQL and PhpMyAdmin databases. This application has been tested using the Black Box Testing method, proving that this application meets needs and is suitable for use.